Social Crisis of Modernity- Collateral Damage - Bauman , Zygmunt; Aneet (Gyan Management Journal, 2014)
Bauman’s latest book is an intellectual stand against the uncertainty and meaninglessness modernity about which he writes. Cutting across djsciplines with rhetoric elegance and stylistic refinement and never in short supply of irony, Bauman refers his readers not only to philosophy and sociology, but also to a broad range of literature and the arts, which he not merely references, but also twists and puts into a new context.The Introduction is a survey of the ’collateral damage of social inequality.’ The first chapter ’From the Agora to the Market Place’ looks into the increasing difficulties the ’social state’ has in solving problems of inequality and envisages ’the social planet’ as a ’vehicle’ that might generate solutions at an ’extraterritorial’ and ’cosmopolitan’ level. After a reconsideration of the possibilities offered by a system that opposes consumerism in ’Requiem for Communism,’ Bauman analyzes ’the fate of social inequality in liquid modern times.’ In ’Consumerism and Morality,’ the author shows how consuming becomes a moral act and a way of connecting and committing to others in societies which have entered a process of serious social disintegration.